Sentinel lymph node status versus tumor characteristics, neutrophil to lymphocyte ratio, C-reactive protein levels and C-reactive protein to albumin ratio-prognostic factors for primary cutaneus melanoma - Stojanoski Sinisa; Manevska, Nevena; Makazlieva, Tanja; Miladinova, Daniela (Springer Science and Business Media LLC, 2019)
Aim/Introduction: The aim of this study was to identify tumor characteristics of primary malignant melanoma, neutrophil to lymphocyte ratio (NLR), C - reactive protein (CRP) levels and C - reactive protein to albumin ratio (CRP/Alb) predictive of sentinel lymph node (SLN) positive status and their impact on disease recurrence, melanoma specific survival (MSS), disease free survival (DFS) and overall survival (OS) period. Materials and Methods: 100 patients with primary malignant melanoma, clinically staged T1b/T2+ (1-4mm thick) N0, M0 underwent SLN detection procedure. Tumor characteristics, NLR, CRP levels and CRP/Alb ratio were analyzed in correlation with SLN status. The optimal cutoff values of NLR and CRP/Alb were determined by the receive operative characteristics (ROC) analysis. Univariate and multivariate Cox regression analyses, t - test for continuous or X2 test for categorical variables and Kaplan-Meier curve analyses were performed to assess factors predicting SLN positive status, regional recurrence rate, DFS, MSS and OS period. Results: We identified Breslow`s thickness (OR=1,51; 95% CI 1,02- 2,01; p=0,034), presence of ulceration (p=0,041), lymphocytic infiltration (OR=0,42; 95% CI 0,18-0,99; p=0,02), high mitotic rate (p=0,031), high Ki67 index (p<0,01), high NLR (HR=2,45; 95% CI 1,52-3,34; p<0,01), increased CRP levels (HR=1,53; 95% CI 1,33-1,75; p<0,001) and high CRP/Alb ratio (HR=2,01; 95% CI 1,15-3,52; p=0,016) as independent predictors of SLN positive status. SLN status was the strongest predictor (HR=0,241; 95% CI 0,45-1,01; p=0,04) of DFS, MSS and OS period. Conclusion: We confirmed Breslow’s thickness, presence of ulceration, lymphocytic infiltration extent, high mitotic rate, high Ki67 index, high NLR, increased CRP levels and high CRP/Alb ratio as factors predictive of SLN metastatic involvement. We also confirmed SLN status to be the most significant independent predictor of DFS, MSS, OS and risk of regional recurrence. Key words: neutrophil to lymphocyte ratio, c - reactive protein to albumin ratio, prognostic factors, melanoma, sentinel lymph node